Utility of 360° Real‐time Endoanal Sonography for Evaluation of Perianal Fistulas. (14th July 2017) - Sun, Yan; Cui, Li‐Gang; Liu, Ji‐Bin; Wang, Jin‐Rui; Ping, He; Chen, Zhao‐Wen
Abstract : Objectives: To assess the diagnostic accuracy and performance of 360° endoanal sonography for preoperative evaluation of perianal fistulas using surgical results as a reference standard. Methods: Between January 2012 and May 2016, 122 patients with suspicious anal fistulas and perianal abnormalities had real‐time endoanal sonographic examinations using a 360° cross‐sectional endoanal transducer (5–13 MHz) for preoperative evaluation of the disease. All patients underwent surgical interventions. The sonographic findings, including the fistulas and other inflammatory lesions, were correlated with surgical results. The types of fistulas on endoanal sonography were compared with the surgical classification of Parks et al ( Br J Surg 1976; 63:1–2), and the internal opening of the fistula on endoanal sonography was confirmed by surgical results as a reference standard. Results: The 122 patients studied included 111 male and 11 female patients. Endoanal sonography was able to show and track hypoechoic lesions, their locations, and internal openings of the fistulas. Compared with surgical results, endoanal sonography had sensitivity of 92.2%, specificity of 100%, and accuracy of 93.4% for the diagnosis of perianal fistulas. Also, endoanal sonography had accuracy of 87.4% for determining fistula types based on the Parks classification and 94.6% for identifying internal openings of the fistulas. Conclusions: Endoanal sonography is an accurate and noninvasive imaging modality for evaluation of fistulas. It is a very useful tool for preoperative management and surgical planning by providing precise and detailed information on fistulas.